Applying Diagnostic Assessment with Rasch Analysis to Measure Students' Basic Understanding of Economics - Neva Lionitha Ibrahim; Lukman Abdul Rauf Laliyo; Radia Hafid; Meyko Panigoro; Frahmawati Bumulo (STKIP Singkawang, 2024)
Reviewing student understanding can be done through the diagnostic assessment process. However, many teachers have difficulty in conducting assessments. Based on the results of the theoretical study, Rasch Model Analysis can make it easier for teachers to conduct diagnostic assessments. Rasch model analysis can be used to measure the effectiveness of items on test instruments, the level of ability of respondents, and detecting differences in ability and item bias. For those reason, researchers conducted a diagnostic assessment to 330 students in 10th grade from three different High Schools in Gorontalo City. The test results processed and analyzed using Rasch modeling. The results was described in this study with a Quantitative Descriptive approach. The purpose of this study is to measure the effectiveness of the test instrument in the diagnostic assessment process, the level of student understanding, and to determine whether there are differences in ability based on gender and school category. This research found that: 1) the test instrument has good validity and reliability; 2) Students' concept understanding ability was divided into: 6% very high, 25% high, 29% medium, 25% low and 15% very low. 3) There was a significant difference between students' understanding based on school origin criteria. The findings of this research are expected to serve as recommendations for future teachers and educational practitioners to integrate diagnostic measurement with the Rasch model in evaluating student understanding.